Compulsion and its impact on marriage contracts - Al-Amri, Reem Rami (Journal of Islamic Sciences, 2019)
In some communities, especially tribal, there is a serious phenomenon that affects the roots of society and its nucleus that is the phenomenon of forcing girls to marry someone that she doesn't like. This phenomenon can make the family destroyed and make it unable to achieve its humanitarian mission. Hence, it is necessary to seek the wise opinion in this matter by knowing the views of the jurists on the coercion of women, in addition to studying the psychological side and how it affects the behavior of women. The study concluded that women must be aware of their legitimate rights, she must have sufficient personal freedom and spend life with her self-satisfaction, women also must have the ability to defend themselves by raising their issue to the judiciary, which in turn criminalizes all those who force women to marry without their consent.
Keywords: Marriage contract; forcing girls; psychological side; judicial